Pengaruh Dukungan Sosial terhadap Manajemen Waktu Peserta Didik Kelas X di SMA N 3 Padang - Elsi Yunarti; Suryadi Suryadi; Mori Dianto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study is motivated by the importance of time management skills for students in supporting academic success and the achievement of academic goals. However, some students still struggle with time management—such as procrastinating on assignments, lacking the ability to prioritize activities, and failing to utilize time effectively. Social support received from family, peers, and teachers is hypothesized to be a factor influencing students' time management. The study aims to: 1) Assess the social support of Grade X students at SMA Negeri 3 Padang; 2) Assess the time management of Grade X students at SMA Negeri 3 Padang; and 3) Examine the influence of social support on the time management of Grade X students at SMA Negeri 3 Padang. This study employs a quantitative descriptive method with regression analysis. A proportional random sampling technique was used to select 81 students from a total population of 439. Questionnaires served as the research instruments, comprising items measuring social support and time management variables. Data analysis included descriptive analysis, prerequisite analysis tests, and simple linear regression analysis. The results indicate that: 1) Student social support falls into the high category (67.90%); 2) Student time management falls into the moderate category (62.96%); and 3) There is a significant influence of social support on the time management of Grade X students at SMA Negeri 3 Padang (significance value of 0.001 < 0.05), leading to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha). The magnitude of the influence of social support on time management is indicated by an R-Square value of 24.5%, implying that social support makes a low contribution to students' time management. Therefore, it is recommended that guidance and counseling teachers, as well as subject teachers, provide services and materials to help elevate the social support received by students from the